Mechanisms of fever-induced QT prolongation and torsades de pointes in patients with KCNH2 mutation - Usuda, Keisuke; Hayashi, Kenshi; Nakajima, Tadashi; Kurata, Yasutaka; Cui, Shihe; Kusayama, Takashi; Tsuda, Toyonobu; Tada, Hayato; Kato, Takeshi; Sakata, Kenji; Usui, Soichiro; Fujino, Noboru; et al. (Europace (London, England), 2023)
Abstract Aims Patients with particular mutations of type-2 long QT syndrome (LQT2) are at an increased risk for malignant arrhythmia during fever. This study aimed to determine the mechanism by which KCNH2 mutations cause fever-induced QT prolongation and torsades de pointes (TdP). Methods and results We evaluated three KCNH2 mutations, G584S, D609G, and T613M, in the Kv11.1 S5-pore region, identified in patients with marked QT prolongation and TdP during fever. We also evaluated KCNH2 M124T and R269W, which are not associated with fever-induced QT prolongation. We characterized the temperature-dependent changes in the electrophysiological properties of the mutant Kv11.1 channels by patch-clamp recording and computer simulation. The average tail current densities (TCDs) at 35°C for G584S, WT+D609G, and WT+T613M were significantly smaller and less increased with rising temperature from 35°C to 40°C than those for WT, M124T, and R269W. The ratios of the TCDs at 40°C to 35°C for G584S, WT+D609G, and WT+T613M were significantly smaller than for WT, M124T, and R269W. The voltage dependence of the steady-state inactivation curve for WT, M124T, and R269W showed a significant positive shift with increasing temperature; however, that for G584S, WT+D609G, and WT+T613M showed no significant change. Computer simulation demonstrated that G584S, WT+D609G, and WT+T613M caused prolonged action potential durations and early afterdepolarization formation at 40°C. Conclusion These findings indicate that KCNH2 G584S, D609G, and T613M in the S5-pore region reduce the temperature-dependent increase in TCDs through an enhanced inactivation, resulting in QT prolongation and TdP at a febrile state in patients with LQT2. Graphical Abstract Graphical Abstract